Methodological Note on EBA-Lite. (Policy Papers; Policy Paper, 2016)
The Fund has taken important steps to enhance its external sector assessments since the launch of the External Balance Assessment (EBA) methodology and the External Sector Report (ESR) in 2012, which provides a multilaterally consistent assessment of the largest economies' external sector positions and policies. With scope for strengthening external sector assessments of non-EBA countries, the 2014 Triennial Surveillance Review (TSR) called for the application of EBA's conceptual innovations to a broader set of countries. Following the 2014 TSR, the Managing Director's Action Plan proposed developing EBA-lite to extend the EBA methodology to a broader group of countries where adequate data is available. In the fall of 2014, the launch of the EBA-lite methodology for current account assessments provided the first extension of EBA approach for non-EBA countries. In summer 2015, the real exchange rate index model and the external sustainability approach were added to the EBA-lite framework. This note serves as a reference for the EBA-lite methodology. It provides: (i) motivations for developing EBA-lite and guidance for its use; (ii) technical explanations of all three EBA-lite approaches; and (iii) suggestions on how to articulate staff assessments of the external sector informed by model results.